Results of the Treatment of Type-C Distal Femoral Fractures using Four Different Implants: Condylar Blade Plate, Dynamic Condylar Screw, Condylar Buttress Plate, and Distal Femoral Locking Plate - Supanich, MD, V (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To evaluate clinical results of surgical treatment of type-C distal femoral fracture using four different types of implants. Material and Method: A retrospective study of 86 patients, all with type-C distal femoral fractures, and who underwent surgery using four different types of implants. The use of condylar blade plate, dynamic condylar screw, condylar buttress plate, or distal femoral locking plate, was evaluated. Following bone union, the functional outcome and the degree of knee flexion were assessed according to Schatzker and Lambert criteria. Results: Good to excellent functional outcomes of the studied group were found in 72% of the 86 patients. Average knee flexion was 108.6 degrees. Among the four different implants, the functional outcomes were as follows: good to excellent results in 89% of the distal femoral locking plate group, in 78% of the dynamic condylar screw group, in 66% of the condylar blade plate group, and in 50% of the condylar buttress plate group. Knee flexion in patients treated with the distal femoral locking plate was significantly superior to that found in those who underwent condylar buttress plate implant. However, there were no significant differences encountered in other paired comparisons. Conclusion: Of the four different implants used in surgical treatment of type-C distal femoral fracture, the distal femoral locking plate fixation implant provided the highest percentage of good to excellent functional outcome, and achieved a better degree of knee flexion than the condylar buttress plate. No significant differences were demonstrated in other paired comparisons.